(untitled) (CIPEEX, 2022)
THE PRESENT STUDY HAS AS ITS CENTRAL OBJECTIVE THE LEGAL AND SOCIAL ANALYSIS OF ACTIVE AGING AND SOCIAL INCLUSION, WITH EMPHASIS ON THE LABOR MARKET. IT WILL ALSO BE OBSERVED THE PRINCIPLES THAT GOVERN THE LEGAL RELATIONSHIP OF THE ELDERLY WITH SOCIAL SECURITY PROTECTION AS WELL AS THEIR OWN LAWS AND STATUTES THAT GRANT RIGHTS TO THIS GROUP. FINALLY, THE STUDY WILL ALSO MAKE AN APPROACH TO PUBLIC POLICIES FOR SOCIAL INCLUSION, ESPECIALLY IN RELATION TO THE LABOR MARKET FOR THE ELDERLY.